2014
DOI: 10.1373/clinchem.2013.213363
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Direct Estradiol Immunoassays with Human Male Serum Samples

Abstract: BACKGROUND:Steroid immunoassays originally required solvent extraction, chromatography, and structurally authentic tracers to avoid interference from steroid cross-reactivity and matrix effects. The demand for steroid assays has driven assay simplification, bypassing this triplet of validity criteria to allow use of unextracted serum, which has introduced bias and nonspecificity at low steroid concentrations. We aimed to evaluate the performance of commercial direct estradiol (E 2 ) immunoassays relative to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 39 publications
1
43
1
2
Order By: Relevance
“…Other previous studies have reported stable serum E 2 levels with regard to male aging using conventional RIAs (38,39,40,46) or GC-MS (43,47,48), whereas studies using direct immunoassays reported no change (49, 50) or a decline (51). Some of these discrepancies are likely due to the unreliability of E 2 immunoassays at the low circulating levels prevailing in men (24,25,26,52 The mechanism and significance of the biochemical decline in androgen status affecting aging men cannot be determined from the present observational study. Nevertheless, an important and plausible explanation is that this decline reflects the impact of the co-morbidities accumulating during aging on an otherwise healthy reproductive system.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Other previous studies have reported stable serum E 2 levels with regard to male aging using conventional RIAs (38,39,40,46) or GC-MS (43,47,48), whereas studies using direct immunoassays reported no change (49, 50) or a decline (51). Some of these discrepancies are likely due to the unreliability of E 2 immunoassays at the low circulating levels prevailing in men (24,25,26,52 The mechanism and significance of the biochemical decline in androgen status affecting aging men cannot be determined from the present observational study. Nevertheless, an important and plausible explanation is that this decline reflects the impact of the co-morbidities accumulating during aging on an otherwise healthy reproductive system.…”
Section: Discussioncontrasting
confidence: 63%
“…Furthermore, serum DHT was rarely measured in population-based studies as few in-house DHT immunoassays were available and none in multiplex or valid single-tube formats (23). Similarly, serum E 2 was usually measured by direct immunoassays, which are inaccurate at the low circulating E 2 levels prevailing in men of all ages (24,25,26). Finally, few studies reported measuring serum testosterone, DHT, and E 2 in studies of thousands of participants (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by an observational study showing elevated risk of stroke with high levels of E2 [36]. Previous studies have mostly relied on E2 measured using immunoassay [11,15,18,19], which has been shown to be unreliable for measurement of E2 in men [22]. Furthermore, studies assessing the association between E2 and carotid plaque in men with CAD are lacking.…”
Section: Discussionmentioning
confidence: 86%
“…These studies of T and E2 consist of heterogeneous populations of men with coronary artery disease (CAD), and are limited by the use of radioimmunoassay for assay of T and E2. More accurate assay of T, and of DHT and E2 can be undertaken using mass spectrometry [21,22]. Studies examining the association of DHT with preclinical carotid atherosclerosis are lacking.…”
Section: Assessment Of Cimt and Carotid Plaquementioning
confidence: 99%
“…Second, sex steroid hormones are known to vary on a diurnal basis, and the use of a single measurement for each of these biomarkers could potentially lead to non-differential misclassification bias. In addition, sex steroid hormones were measured by immunoassays and vitamin D was measured using DiaSorin(rather than mass spectrometry) which are now widely understood to be suboptimal for clinical research involving women, children or men with low serum testosterone [44,45] and especially for serum estradiol in men [46,47]. However, previous studies have indicated an association between testosterone levels and adverse events, irrespective of whether immunoassays or mass-spectrometry measurements were applied [5,14,15].…”
Section: Discussionmentioning
confidence: 99%